Cervical spine surgery in patients with rheumatoid arthritis: an appraisal. Issue 2 (February 1996) - McRorie, E R; McLoughlin, P; Russell, T; Beggs, I; Nuki, G; Hurst, N P
Abstract : OBJECTIVES: To review the outcome of surgery undertaken to stabilise the neck in patients with rheumatoid arthritis performed over a five year period, to compare the results with those of previous reports, and to identify factors that may predict surgical outcome. METHODS: Outcome was assessed at time of discharge from hospital after surgery by review of patients' notes, and at follow up by patient interview, clinical examination, anonymous questionnaire, and cervical spine radiograph. The Ranawat classification of neurological impairment and Steinbrocker functional classification were used. RESULTS: Thirty nine patients underwent 44 procedures; 28 patients were available for review after a mean period of 29.8 months (range 12-65 months). Fourteen patients had preoperative neurological impairment and were available for follow up; 13 returned the questionnaire. Four (29%) had improved Ranawat class, nine were unchanged, and one had deteriorated. Nine (69%) reported a subjective improvement in neurological symptoms by questionnaire, even though the Ranawat class was unchanged in five. Twenty five of the patients reviewed had pain before operation; 21 returned the questionnaire. Pain relief was reported by direct questioning and questionnaire in 76% and 67% of patients, respectively. Overall, 67% felt that surgery had been successful. Surgery was more successful in producing symptomatic relief in patients with neck or radicular pain than in those with neurological deficit, but did prevent progression of neurological symptoms. CONCLUSIONS: Our results are similar to those from other centres. Overall patient satisfaction with surgery was good. Surgery was more likely to produce symptomatic relief in patients with neck or radicular pain before operation than in those with neurological deficit. The greater subjective improvement in neurological symptoms as judged by questionnaire probably reflects the relative insensitivity of the Ranawat classification in detecting change in neurological status; previous reports of poor outcome for patients with neurological symptoms who undergo surgery may in part be a reflection of the insensitivity of this method of assessment. No clear factors emerged which allowed prediction of those patients at greatest risk of operative mortality. In particular, an increased risk of neurological compromise appeared to confer no additional risk of immediate perioperative death. Our data support the suggestion that early surgery to correct symptomatic atlantoaxial subluxation may prevent progression of instability.